The Little Green Data Book 2012. - Bank, World (Online access: World Bank World Bank Open Knowledge Repository., 2012)
Health insurance can offer protection against catastrophic medical expenses and improve access to health care. There are, however, imperfections in the insurance market that require intervention such as asymmetry of information between the policy holder and the insurance company, moral hazard that can occur on the side of the insured or the provider of health services, risk selection that may lead to cream skim a particular market, and others. To encourage the effective development of Voluntary Private Health Insurance, it will be necessary for policymakers to establish and enforce regulatory.